Advances in chitosan biopolymer composite materials: from bioengineering, wastewater treatment to agricultural applications. (1st May 2022) - Chadha, Utkarsh; Bhardwaj, Preetam; Selvaraj, Senthil Kumaran; Kumari, Kanak; Isaac, Tassella Susanna; Panjwani, Mahek; Kulkarni, Kunal; Mathew, Rhea Mary; Satheesh, Ashly Mariam; Pal, Anushka; Gunreddy, Neha; Dubey, Omika; et al.
Abstract: Chitosan has become the most known and second abundantly available recyclable, non-hazardous and eco-friendly biopolymer after cellulose with several advantageous biomedical, agriculture, and wastewater treatment applications. As nanotechnology has progressed, researchers have begun incorporating chitosan-based carbon compounds into various compounds, elements, and carbonaceous materials to increase their efficiency and biocompatibility. Chitosan carbon compounds have also been used directly in many applications due to their inherent chelating and antibacterial features and the presence of customizable functional groups. This review widely discusses- the properties and synthesis of chitosan and chitosan composite. It also discusses the modification of chitosan with different compounds, metals, carbonaceous materials, and agriculture residues to allow their use on an industrial scale. Recent advances in the use of chitosan in biomedical, agro-waste management, agriculture, wastewater treatment, and a few other applications (such as food packaging, cosmetics, and the textile and paper sector) are briefly discussed. Furthermore, this analysis reveals that chitosan and its composite materials are potential, low-cost products for environmental clean-up that can be made with basic manufacturing procedures.